PENGARUH DESAIN PRODUK T-SHIRT FORGOTTEN BAND DI REMAINS STORE TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN - Ajeng Maulidari; Muhammad Irsyad Raspati; Sri Maria Ulfha (LPPM STIKes SITI HAJAR dan Insight Power, 2022)
The purpose of this research is to identify the influence of product design for Forgotten Band t-shirt to the consumer’s buying descision. The method used in this research is quantitative method. Data analysis conducted using simple correlation test and simple regression test. Research result indicates r = 0.86, which means there is very strong correlation between product design with the consumer’s buying decision. Coefficient of Determinants is 75.3%, which indicates that there is 75.3% contribution of product design to buying decision, and the other 24.3% is unknown. Regression formula is Y=0.293+0.621X, which means in every one point change in produt design, there will be 0.293 increase in buying decision. Based on the result in this research, conclusion is made that the product design of Forgotten Band t-shirt has significant influence in the customer’s buying decision,Keywords: Product, Product Design, Consumer, Buying, Buying Decision